POTRET KOMPETENSI INTELEKTUAL PELAKU UKM DALAM UPAYA PENINGKATAN KINERJA USAHA - Tati Haryati; Melinda Melinda; Rukun Santoso; A. Besse Dahliana; Suwandi Suwandi (Komitmen: Jurnal Ilmiah Manajemen, 2023)
Intellectual competency is an important element in the successful management of Small and Medium Enterprises (SMEs), whose applications are still not optimally empowered by SMEs in Indonesia. This case study aims to describe the forms of intellectual competence of UKM actors and their empowerment in achieving UKM performance in Nagauleng Village, Cenrana District, Bone Regency. This study involved 3 UKM actors who were selected using purposive sampling. Data collection techniques using interviews and documentation. The collected data is processed using a data triangulation approach with stages: data reduction, data presentation, and conclusion and verification. This study found forms of SME intellectual competence, including: creativity skills, innovation skills, skills in preparing business plans, and job evaluation skills. Furthermore, empowering intellectual competence can improve the performance of SMEs. Following up on these findings, it is very important to implement various intellectual competencies in the management of SMEs so as to provide opportunities to achieve maximum performance.